Cellular constituents and structural organization of the bovine thymus and lymph node - Morrison, W. Ivan; Lalor, P.A.; Christensen, A.K.; Webster, P. (Cambridge University Press, 1986)
The thymus is concerned with the production of functionally mature T cells. In cattle, it consists of two lobes, each composed of multiple lobuleswith distinct cortical and medullary regions. The thymus is supported by a network of epithelial cells; in the cortex, these are delicate spindle-shaped cells which express high levels of class II MHC antigens but little or no class I antigen, whereas, in the medulla they are more pleomorphic and are rich in both class I and class II MHC antigens. The medulla also contains a population of interdigitating cells which express high levels of class II MHC antigens. The cortical lymphocytes, which make up about 85% of thymic lymphocytes; are largely negative for class I and class II MHC antigens and exhibit high affinity for the lectin, peanut agglutinin (PNA), whereas the medullary lyphocytes express detectable levels of class I MHC antigens, are negative for class II antigens and show low affinity binding of PNA. In cattle, as in other species, the structure of the lymph node is adapted to trapping and responding to foreign material which gains access to the lymphatic system. The lymph nodes possess a structural framework of reticulum cells and reticulin fibres permeated by sinuses which are also lined by reticulum cells. The solid lymphoid tissue is segregated into follicular areas, populated predominantly with B cells, and paracortical areas containing mainly T cells. Each compartment contains specialized accessory cells, namely, the follicular dendritic cells and the interdigitating cells of the papcortex. The latter, along with B cells express high levels of class II MCH antigens, whereas class I antigens are expressed on all of the cellular constituents, although they appear to be present at much lower concentrations on germinal centre lymphoblasts.